History of the development of religious organizations in Central Kazakhstan - Zharas Kenzhegali, Kanat Bodeyev, Zauresh Saktaganova, Assel Myrzakhmetova, Shamil Ilyassov, (Opción, 2019)
The article studies the development of religious organizations in Central Kazakhstan during the Second World War and after its end, the role in the life of the Soviet man via the method of systematization, induction, and deduction. As a result, the all-Union organization Union of hostile atheists, which fought against religion for twenty years, was silent during the war. In conclusion, in Central Kazakhstan, religious associations were removed from the inventory. The struggle of local authorities with religion was without any particular imposition, but was known for systemic confrontation with each other.